JUNGBRUNNEN1 Confers Drought Tolerance Downstream of the HD-Zip I Transcription Factor AtHB13 - Ebrahimian-Motlagh, Saghar; Ribone, Pamela A.; Thirumalaikumar, Venkatesh P.; Allu, Annapurna D.; Chan, Raquel L.; Mueller-Roeber, Bernd; Balazadeh, Salma (Frontiers in Plant Science, 2017)
Low water availability is the major environmental factor limiting growth and productivity of plants and crops and is therefore considered of high importance for agriculture affected by climate change. Identifying regulatory components controlling the response and tolerance to drought stress is thus of major importance. The NAC transcription factor JUNGBRUNNEN1 (JUB1) from Arabidopsis thaliana extends leaf longevity under non-stress growth conditions, lowers cellular hydrogen peroxide (H2O2) level, and enhances tolerance against heat stress and salinity. Here, we additionally find that JUB1 strongly increases tolerance to drought stress in Arabidopsis when expressed from both, a constitutive (CaMV 35S) and an abiotic stress-induced (RD29A) promoter. Employing a yeast one-hybrid screen we identified HD-Zip class I transcription factor AtHB13 as an upstream regulator of JUB1. AtHB13 has previously been reported to act as a positive regulator of drought tolerance. AtHB13 and JUB1 thereby establish a joint drought stress control module.